Will the Train Ever Leave the Station? The Private Provision of Freight Railway Service in Russia and Central and Eastern Europe - Russell Pittman; Oana Diaconu; Emanual Šip; Anna Tomová; Jerzy Wronka (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
The railways of Russia and the CEE countries — generally much more freight oriented, and much more important to their countries' economies, than those of Western Europe — are in the process of restructuring. In most cases the "vertical separation" reform model is being pursued, and reformers are seeking to introduce competition among freight train operators through the provision of "open access" to the monopoly infrastructure. This paper examines the degree to which competition has in fact been introduced, the terms under which it is taking place, and the characteristics of those private firms which have had some success in entering. As always, Russia is different.
Keywords: 330